Hemophilia B with Mutations at Glycine-48 of Factor IX Exhibited Delayed Activation by the Factor VIIa-tissue Factor Complex - Wu, Pai-Chih; Hamaguchi, N.; Yu, Yi-Shing; Shen, Ming-Ching; Lin, Shu-Wha (Thrombosis and Haemostasis, 2000)
Gly-48 is in the conserved DGDQC sequence (residues 47-51 of human factor IX) of the first EGF (EGF-1)-like domain of factor IX. The importance of the Gly-48 is manifested by two hemophilia B patients; factor IXTainan and factor IX>Malmö27, with Gly-48 replaced by arginine (designated IXG48R) and valine (IXG48V), respectively. Both patients were CRM+ exhibiting mild hemophilic episodes with 25% (former) and 19% (latter) normal clotting activities. We characterize both factor IX variants to show the roles of Gly-48 and the conservation of the DGDQC sequence in factor IX. Purified plasma and recombinant factor IX variants exhibited approximately 26%–27% normal factor IX’s clotting activities with G48R or G48V mutation. Both variants depicted normal quenching of the intrinsic fluorescence by increasing concentrations of calcium ions and Tb3+, indicating that arginine and valine substitution for Gly-48 did not perturb the calcium site in the EGF-1 domain. Activation of both mutants by factor XIa appeared normal. The reduced clotting activity of factors IXG48R and IXG48V was attributed to the failure of both mutants to cleavage factor X; in the presence of only phospholipids and calcium ions, both mutants showed a 4∼7-fold elevation in Km, and by adding factor VIIIa to the system, although factor VIIIa potentiated the activation of factor X by the mutants factor IXaG48R and factor IXaG48V, a 2∼3-fold decrease in the catalytic function was observed with the mutant factor IXa’s, despite that they bound factor VIIIa on the phospholipid vesicles with only slightly reduced affinity when compared to wild-type factor IXa. The apparent Kd for factor VIIIa binding was 0.83 nM for normal factor IXa, 1.74 nM for IXaG48R and 1.4 nM for IXaG48V. Strikingly, when interaction with the factor VIIa-TF complex was examined, both mutations were barely activated by the VIIa-TF complex and they also showed abnormal interaction with VIIa-TF in bovine thromboplastinbased PT assays. Taken together, our results suggest that mutations at Gly-48 altered the interaction of factor IX with its extrinsic pathway activator (VIIa-TF complex), its macromolecular substrate (factor X), and its cofactor (factor VIIIa).
Keywords: Hemophilia B; factor IX; Gly-48; mutagenesis